KORELASI PENGUASAAN TEORI PUISI DENGAN KETERAMPILAN MENULIS PUISI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS BAHASA DAN SASTRA UNIVERSITAS NEGERI MAKASSAR ANGKATAN 2015 - Aswati Asri (Universitas Negeri Makassar, 2017)
Abstract. The Correlation Between Theory Of Poetry and Writing A Poem of The Students’ in Indonesia Language Education and Literature Study Program Academic Year 2015. An Article. Indonesia Language And Literature Department, State University Of Makassar. The purpose of this research was to determine the level of correlation between theory of poetry mastery and students’ writing poem skill in Indonesia language education and literature study program academic year 2015. The type of this research is correlation. The data analysis used inferential statistic method, which applied coeficient correlation of product moment. The population was 105 students of Indonesia language education and literature study program language and literature faculty of state university of Makassar in academic year 2015 with 22 samples (25% of students population). The technique of data collection was used objective test and assignment. Theory of poetry test was used to determine the level theory of poetry mastery (x variable) and poetry writing assignment to determine the level of poetry writing skill (y variable) of Indonesia language education and literature study program language and literature faculty of state university of Makassar in academic year 2015. The test result from poetry writing assignment (y) showed that students had average scores 6,4. The data analysis showed that r count was bigger or same as r table (rt = 0,571) (rt = 0,325) in significance level of 95%. The research result showed that theory of poetry test had a significance correlation between theory of poetry mastery and students’ writing poem skill in Indonesia language education and literature study program academic year 2015.